2019
DOI: 10.3390/ijerph16020188
|View full text |Cite
|
Sign up to set email alerts
|

Crude Oil Degrading Fingerprint and the Overexpression of Oxidase and Invasive Genes for n-hexadecane and Crude Oil Degradation in the Acinetobacter pittii H9-3 Strain

Abstract: A crude oil-degrading bacterium named strain H9-3 was isolated from crude oil contaminated soil in the Northeastern area of China. Based on its morphological characteristics and 16S rDNA sequence analysis, strain H9-3 is affiliated to Acinetobacter pittii in the group of Gammaproteobacteria. The strain was efficient in removing 36.8% of the initial 10 g·L−1 of crude oil within 21 days. GC-MS was performed and a preference was shown for n-C10, n-C11, i-C14, i-C17, i-C34, n-C12, n-C13, n-C14, n-C27, n-C32 and i-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Oxygenases are a class of mostly intracellular enzymes that perform functions crucial to biosynthesis and metabolism. Apart from their use in the fabrication of pharmaceuticals and the synthesis of specialty chemicals [37], they derive relevance in the biodegradation of hydrocarbons and their analogous compounds [38] that have been considered environmental pollutants, consequent of their improvident use, storage and disposal: a process generally regarded as biotransformation. Correspondingly, biotransformation via oxygenases is consdered ideal for three salient reasons among other things:The non-existence of their chemical counterparts or lack of the requisite regio- and stereoselectivity.The availability of molecular oxygen as a cheap environmentally benign oxidant in contrast to harsh chemical oxidants [39].…”
Section: Oxidative Enzymesmentioning
confidence: 99%
“…Oxygenases are a class of mostly intracellular enzymes that perform functions crucial to biosynthesis and metabolism. Apart from their use in the fabrication of pharmaceuticals and the synthesis of specialty chemicals [37], they derive relevance in the biodegradation of hydrocarbons and their analogous compounds [38] that have been considered environmental pollutants, consequent of their improvident use, storage and disposal: a process generally regarded as biotransformation. Correspondingly, biotransformation via oxygenases is consdered ideal for three salient reasons among other things:The non-existence of their chemical counterparts or lack of the requisite regio- and stereoselectivity.The availability of molecular oxygen as a cheap environmentally benign oxidant in contrast to harsh chemical oxidants [39].…”
Section: Oxidative Enzymesmentioning
confidence: 99%
“…Acinetobacter sp. strains act as the best decomposers for bioremediation of oil-contaminated sites [25]. It was also found that when using Acinetobacter pitti.…”
Section: Discussionmentioning
confidence: 93%